Acute Kidney Injury Following Resuscitative Endovascular Balloon Occlusion of the Aorta: A Systematic Review - Hoareau, Guillaume L; Cassiday, Patrick A; Stewart, Ian J; Studer, Amy C; DuBose, Joseph J; Neff, Lucas P; Williams, Timothy K; Johnson, M Austin (Journal of Endovascular Resuscitation and Trauma Management, 2018)
Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an emergent technology for the treatment of non-compressible torso hemorrhage (NCTH). While aortic occlusion (AO) above the site of hemorrhage provides hemostasis and time for surgical intervention, ischemia-reperfusion injury to the kidneys is a known complication. We aimed to report the incidence and factors associated with acute kidney injury (AKI) following AO in patients with NCTH or in similar porcine models. Methods: We searched Pubmed (MEDLINE), Embase, Scopus, and ProQuest Dissertations & Theses from inception to July 2017. We included original studies of trauma patients with NCTH treated with REBOA, or similar porcine studies that included renal parameters, excluding case reports and case series. After duplicate removal, full texts of studies retrieved via the search strategy were evaluated by two authors. Renal parameters (e.g., creatinine concentration, urine output, histopathology) were extracted. Quality of the evidence and risk of bias were assessed. Results: Twelve out of 2,100 records were included (three trauma patients, nine porcine studies). While one out of three human reports described AO in Zone 1, all swine publications reported Zone 1. All human studies reported renal damage. There were nonetheless inconsistencies in definitions used. Evidence of AKI was reported in three out of nine swine studies. Conclusions: Consistent reporting of AKI incidence is lacking from human clinical studies of AO in NCTH trauma patients. While comorbidities in trauma patients may contribute to AKI, animal models support the association between AO and AKI. As REBOA is growing in popularity as a therapy for NCTH, further studies determining factors associated with the AKI are needed.